Cellular responses to Cd, Pb and Zn in shrews (Myosorex varius and Crocidura flavescens) and BALB/c mice - Chapman, Aletia Ann (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2000.